Diamond micro-milling of lithium niobate for sensing applications. (1st July 2016) - Huo, Dehong; Choong, Zi Jie; Shi, Yilun; Hedley, John; Zhao, Yan
Abstract: Lithium niobate (LiNbO3 ) is a crystalline material which is widely applied in surface acoustic wave, microelectromechanical systems (MEMS), and optical devices, owing to its superior physical, optical, and electronic properties. Due to its low toughness and chemical inactivity, LiNbO3 is considered to be a hard-to-machine material and has been traditionally left as as an inert substrate upon which other micro structures are deposited. However, in order to make use of its superior material properties and increase efficiency, the fabrication of microstructures directly on LiNbO3 is in high demand. This paper presents an experimental investigation on the micro machinability of LiNbO3 via micro milling with the aim of obtaining optimal process parameters. Machining of micro slots was performed on Z -cut LiNbO3 wafers using single crystal diamond tools. Surface and edge quality, cutting forces, and the crystallographic effect were examined and characterized. Ductile mode machining of LiNbO3 was found to be feasible at a low feed rate and small depth of cut. A strong crystallographic effect on the machined surface quality was also observed. Finally, some LiNbO3 micro components applicable to sensing applications were fabricated.